Desempenho acústico de cortinas em um ambiente de sala de aula - Breginski, Tatiane Bonfim (2021)
The acoustic conditioning of environments plays a fundamental role in the well-being and health of users. Several solutions are used for this purpose, such as the treatment of walls, ceilings, floors and also the use of special frames. Considering that the greatest loss of acoustic insulation within a building occurs in the openings and that an acoustically adequate environment is essential for good learning, there is a need for alternative treatments, which are inexpensive and easy to install for school environments. Thus, this work aims to characterize the acoustic performance of curtains in a classroom environment. For this, sound absorption measurements of different materials were made in an impedance tube, to facilitate its characterization. Subsequently, a threedimensional simulation of the classroom was performed using the ISIMPA software for comparisons between materials. And finally, impulse response measurements were taken in the classroom with certain curtains. A reduction of up to 38% in the reverberation time at a given frequency was observed with the addition of curtains in the environment. There was also a reduction ranging from 21.7% to 41.4% in the average reverberation time from the room without curtains to the room with curtains. Showing that even open, curtains have a significant impact on the acoustics of the environment and not only can, but should also be used for the acoustic conditioning of classrooms.